The discursive (re)construction of social relations in a crisis situation: A genre analytical approach to press conferences on COVID-19 in China - Wang, Hong; Ge, Yunfeng (Frontiers in Psychology, 2022)
The outbreak of COVID-19 has imposed a great threat both to people’s health and to social relations. By following the theoretical constructions of critical genre analysis and critical discourse analysis and drawing on the 35 press conferences on the COVID-19 outbreak in China, this paper explores how the discourse of press conferences is used by the Chinese government as a means of crisis management to (re)construct social relations. The analysis of the data reveals a hybridity of social relations reproduced discursively between such social actors as government institutions, the general public, medical institutions or staff, and COVID-19 patients, and a distinct feature of interdiscursivity of the discourse of press conferences on COVID-19, with descriptive, instructional, strategic, and evaluative discourses being the most frequently employed. It is also found that political, professional, social, and cultural forces are interwoven with each other to contribute to the interdiscursivity of the discourse of press conferences and the hybridity of social relations constructed thereof.